PERSEPSI ANGGOTA TERHADAP GAYA KEPEMIMPINAN PENGURUS DI HIMPUNAN MAHASISWA TAPANULI BAGIAN SELATAN (HIMATABAGSEL) SEKRETARIAT JALAN SWAKARYA KECAMATAN TAMPAN PEKANBARU - Maslatipah Harapap; Aswandi Bahar; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out Member Perceptions of the Leadership Style of the Executive Board of the Southern Tapanuli Student Association (Himatabagsel) Secretariat of Jalan Swakarya Kecamatan Tampan Pekanbaru. The formulation of the problem of this research is What is Member Perceptions of Leadership Style of Management In The Southern Tapanuli Student Association (Himatabagsel) Secretariat of Jalan Swakarya Tampan Pekanbaru and Subdistrict. The population in this study were 115 people. To determine the sample of this study, researchers used Slovin formula with a sample size of 51 people. then the researchers determine the sample using simple random sampling technique (simple random sampling), and 20 people for the sample questionnaire test. The type of this research is descriptive with quantitative approach. Data collection instrument is a questionnaire with 43 statements and after the trial remaining 39 valid statements to be used as research instruments. Data analysis through quantitative descriptive analysis. The findings of this study indicate that Member Perceptions of Leadership Style of Management In The Southern Tapanuli Student Association (Himatabagsel) Secretariat of Jalan Swakarya Kecamatan Tampan Pekanbaru is the highest Democratic Leadership Style with percentage of 79.2%.Keywords: Leadership Style